2019
DOI: 10.3389/fneur.2019.00907
|View full text |Cite
|
Sign up to set email alerts
|

Sequelae and Quality of Life in Patients Living at Home 1 Year After a Stroke Managed in Stroke Units

Abstract: Introduction: Knowledge about residual deficiencies and their consequences on daily life activities among stroke patients living at home 1-year after the initial event managed in stroke units is poor. This multi-dimensional study assessed the types of deficiencies, their frequency and the consequences that the specific stroke had upon the daily life of patients. Methods: A cross-sectional survey, assessing, using standardized scales, 1 year post-stroke disabilities, limitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 28 publications
(21 reference statements)
2
28
1
4
Order By: Relevance
“…All patients living with at least one relative had significantly higher SSQOL indices than those living alone or in nursing homes. Our research data are similar to the results of a study conducted in Portugal and Luxembourg that demonstrated a strong correlation between patient satisfaction and family integration in aphasia rehabilitation therapy [49] as well as other works [59][60][61][62].…”
Section: Discussionsupporting
confidence: 89%
“…All patients living with at least one relative had significantly higher SSQOL indices than those living alone or in nursing homes. Our research data are similar to the results of a study conducted in Portugal and Luxembourg that demonstrated a strong correlation between patient satisfaction and family integration in aphasia rehabilitation therapy [49] as well as other works [59][60][61][62].…”
Section: Discussionsupporting
confidence: 89%
“…13 Post-stroke fatigue is one of the most disabling symptoms in stroke survivors; it reduces the quality of life, increases mortality, and is a barrier to stroke rehabilitation, and has also been shown to affect patients' return to working life. 14,15 In addition, health professionals still lack a regimen or a coping strategy to equip the patient with at discharge from hospital. 16 Efficient management of post-stroke fatigue should be a priority in stroke rehabilitation given the incidence of stroke and the prevalence and detrimental impact of poststroke fatigue on independent living and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…PSF is linked to undesirable stroke outcomes and affects patients’ participation in studies, adherence to medication, and effectiveness of rehabilitation 3 . This has a negative impact on patients’ quality of life and daily life activities 4 7 , and also contributes to the burden on family members and carers 8 .…”
Section: Introductionmentioning
confidence: 99%